Influence of Brahminic Hegemony on folk art Theyyam: Historical analysis of Theyyam myths and socio-cultural events in Northern Kerala - Anurag NT
Theyyam is an art form that blends Tribal, Aryan and Dravidian elements. It is performed annually in the districts of Northern Kerala from October to May. The rich cultural history of Theyyam gives an insight into the cultural ethos and social reality from the 12 th century AD. Theyyams are performed by the members of the untouchable castes. The performer after his transformation is seen as a ‘god’ by the people and at this point he transcends the boundary of the rigid caste system. ‘Thottams’ are the myths that are sung during the performance. This paper attempts a close analysis of the ‘Thottams’, which are unbiased but distorted sources of evidence that gives a portrait of the oppression faced by the lower castes during the 12 th century. Theyyam as it is known today was shaped by various historical incidents and these incidents changed the manner of hegemony exercised by the higher castes over centuries. The major historical incidents that paved way for cultural reform in the state had their influence on Theyyam which helped the art form transform from a ritual into a theatrical performance